An Investigation of University Students' Sustainable Earthquake Awareness Levels in Terms of Different Variables - Murat Genç; Erol Sözen (Sakarya University Journal of Education)
Earthquakes have a significant impact on social, economic, and educational aspects of life. The negative effects of earthquakes on education and training are well documented. It is crucial to be adequately prepared to minimize these effects. This study aims to investigate the earthquake awareness of university students from a sustainable perspective. The survey model, a quantitative research method, was employed in this study. The research study comprised of 200 male (36.10%) and 354 female (63.90%) students who voluntarily participated from a university in the Western Black Sea Region during the 2022-2023 academic year. The Sustainable Earthquake Awareness Scale results show an average of 3.23 (Undecided) for the first factor, Earthquake Structure Relationship, 2.32 (Disagree) for the second factor, Earthquake Preparation Application, and 2.27 (Disagree) for the third factor, Earthquake Preparedness. The overall mean of the scale was 2.61 (Undecided). The results indicate that university students are not adequately prepared for possible earthquakes. There is no significant difference in Sustainable Earthquake Awareness Levels between male and female university students in all sub-factors and the total scale. Furthermore, as the grade level of university students increases, their sustainable earthquake awareness also increases. Furthermore, there is a notable contrast in the earthquake awareness levels of students from the faculties of engineering, health, and theology, with engineering students exhibiting a higher level of awareness. The study found no statistically significant difference between the sustainable earthquake awareness levels of university students and the number of floors in the building where they reside, both in terms of sub-factors and the overall scale.